MENINGKATKAN KOMPETENSI PROFESIONAL GURU DALAM MENERAPKAN METODE PEMBELAJARAN RESITASI MELALUI WORKSHOP - Irwansyah Nur (JURNAL PENDIDIKAN IPS, 2023)
This research aims to improve teachers' professional competence in implementing the Recitation Learning Method through workshops at Dharma Bakti Private High School, SMAN 1 Namorambe, SMAS Nusantara Lubuk Pakam. The method used in this research is the school action research method through 2 cycles, where each cycle has stages: (1) Planning, (2) Implementation and Observation, (3) Evaluation and (4) Reflection. The subjects in this research were teachers who taught at Dharma Bakti Private High School, SMAN 1 Namorambe, SMAS Nusantara Lubuk Pakam with a total of 40 teachers. The data collection techniques used were observation, interviews, questionnaires and documentation studies. The data analysis technique used in this research is to calculate the percentage of the number of teachers who have been able to apply the Recitation Learning Method and the percentage of the number of teachers who have not been able to apply the Recitation Learning Method in the classroom. The research results show: (1). There was an increase in the number of teachers who applied the Recitation Learning Method from 40 teachers, only 30 (75.0%) teachers applied the Recitation Learning Method in cycle I then increased in cycle II to 36 (90.02%) teachers who were able to apply the Learning Method Recitation of the learning process in the classroom; (2) There was a decrease in the number of teachers who were unable to apply the Recitation learning method, out of 40 teachers, as many as 10 (25%) teachers were not able to apply the Recitation Learning Method in cycle I then in cycle II there was a decrease in the number of teachers who were not able to apply the Recitation Learning Method Recitation, there are 4 (10.0%) teachers who have not been able to implement the Recitation Learning Method completely; (3) Teachers' professional competence in implementing the Recitation Learning Method can be improved through workshops.